Indian Constitution and its Basic Structure - Kumar Gautam, Surendra (International Journal of Law, Human Rights and Constitutional Studies, 2022)
The basic structure of Indian constitution or doctrine applies during the time of amendments in constitution of India. The Indian constitution is the worlds longest for a sovereign nation. It is very difficult to state a single and accurate definition of the term “law” as it is a general term and has different connotations for different people. The Supreme Court recognized Basic Structure concept for the first time in the historic Kesavananda Bharati case in 1973. “If the historical background, the preamble, the entire scheme of the constitution and the relevant provisions thereof including article 368 are kept in mind then there can be no difficulty, in determining what are the basic elements of the basic structure of the constitution. These words apply with greater force to doctrine of the basic structure, because, the federal and democratic structure of the constitution, the separation of powers, the secular character of our state are very much more definite than either negligence or natural justice. In this paper we highlight the basic element of Constitutions and its implications.